PELAKSANAAN PERATURAN PEMERINTAH NOMOR 53 TAHUN 2010 TENTANG DISIPLIN PEGAWAI NEGERI SIPIL DALAM KESANGGUPAN UNTUK MENAATI KEWAJIBAN DAN MENGHINDARI LARANGAN DI KANTOR BADAN KEPEGAWAIAN DAERAH PROVINSI RIAU TAHUN 2018 - Syafriadi "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
There are still many violations of discipline of Civil Servants that have been processed by BKD Riau Province during 2013 until July 2018 there were 48 cases. In general, the implementation of PP No. 53 Tahun 2010 concerning PNS discipline in Riau Province has run quite well. Meanwhile enforcement PP. 53 of 2010 has also been implemented with strategies adopted by each SKPD, BKD, and Inspectorate. Supervision of the implementation of PP No.53 of 2010 has also been carried out in Riau Province to reduce the occurrence of disciplinary violations. Supervision is carried out by direct superiors in collaboration with BKD and Inspectorate of Riau Province. There are 4 (four) factors that influence the implementation of PP No. 53 Tahun 2010 concerning PNS discipline in Riau Province namely; 1). Cultural factors that influence the implementation of PP No. 53 Tahun 2010 on civil servant discipline are culture and will become an obstacle if there is no effort to arouse and increase community awareness and participation in social control. 2). Communication factors that support the implementation of PP No. 53 Tahun 2010 such as with general socialization to all SKPDs and with consistency in delivering messages and can hamper the implementation of PP No. 53 Tahun 2010 such as the implementers and civil servants who have just joined the government in Riau Province who have not mastered information about PP No. 53 Tahun 2010. 3). The supporting resource factor is the presence of PP No. 53 Tahun 2010 staff or implementers who have quite high education in the Riau Province government and the obstacle is the availability of PP No. 53 Tahun 2010 implementers whose numbers are still lacking to enforce PNS discipline in Riau Province. 4). These bureaucratic structure factors such as the existence of clear division of authority between the implementers of the policy with one another that has been clearly regulated in the main tasks and functions of each implementing agency Keywords: Work Culture, Bureaucracy, Communication, Oversight System, Employee Coordination